A Correlation Study on Human Factors Value among AEB Equipped Vehicle Users: Experience and Satisfaction - N. M. Ishanuddin; E. H. Sukadarin; M. Widia; N. S. Fauzan; J. Zakaria; H. Abdul Aziz; H. Osman; A. A. Ab. Rashid; N. S. Mohd Nawi; E. N. Roslin; Yassierli (Journal of the Society of Automotive Engineers Malaysia, 2022)
The Autonomous Emergency Braking (AEB) system in a car has had great potential to prevent traffic accidents since its introduction in the past years. It is one of the safety systems embedded in the vehicle that can oversee the impending forward crash, which automatically brakes the car when sensing a collision threat. This safety system is available in specific vehicle models that can be opted for by vehicle users. Thus, the functionality of this system can be studied in terms of human acceptance and satisfaction. Objectives: This paper intends to investigate the relationship between the car models equipped with the AEB system and the perceived value construct under study. Methodology: A cross-sectional study was conducted among AEB system users’ that experienced the AEB operation. Using the data, descriptive and correlation analyses were used to investigate the relationship between the construct under study. Result: There is a significant relationship between perceived value and vehicle models. Conclusion: This paper aid car manufacturers to fulfil the users’ needs and satisfaction regarding AEB function and benefits. New technologies can be tested for human satisfaction and acceptance of the systems operations in a vehicle. Future research regarding human and technology acceptance can be conducted extensively.